‘Happy slaves’?: the adaptation problem and identity politics in the writings of Amartya Sen - Burns, Tony (Emerald, 2016)
This paper examines the relationship between Amartya Sen’s notion of adaptation and his views on identity politics by focusing on the issue of slavery and, more specifically, on the example of the happy or contented slave. The methodological approach adopted is that of conceptual analysis, as is typical for work of this kind. The paper concludes that the example of the happy or contented slave is indeed a fruitful one for those interested in exploring the relationship between Sen’s views on ‘the adaptation problem’ and his views on identity politics, especially in relation to the subjection of women. Here Sen’s debt to the ideas of Mary Wollstonecraft and John Stuart Mill is particularly important. One implication of the argument of the paper is that there is a need to consider more carefully the differences that exist between the views of Wollstonecraft and Mill, so far as the example of the happy or contented slave is concerned. One practical implication of the paper is that, hopefully, it establishes the continued relevance of the ideas of thinkers such as Wollstonecraft and Mill today, not least because of the influence that they have had on theoreticians such as Amartya Sen. The paper addresses issues which are of considerable social and political significance, especially for women in underdeveloped societies today. The example of the happy or contented slave has not received much discussion in the literature on Sen, although Sen himself has suggested that the distinction between happiness and contentment is an important one, which does merit further discussion.